2014
DOI: 10.1002/ca.22354
|View full text |Cite
|
Sign up to set email alerts
|

Venous drainage of the spine and spinal cord: A comprehensive review of its history, embryology, anatomy, physiology, and pathology

Abstract: Venous drainage of the spine and spinal cord is accomplished through a complex network of venous structures compartmentalized to intrinsic, extrinsic, and extradural systems. As the literature on this topic is scarce, the following review was performed to summarize the available literature into a single coherent format. The medical literature on the spinal venous system was reviewed using online sources as well as historical documents that were not available online in regard to history, embryology, anatomy, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 65 publications
(148 reference statements)
0
41
0
1
Order By: Relevance
“…However, a different study showed that reperfusion of the cord after a compressive insult is not accompanied by the recovery of evoked potentials (Hitchon et al, ). Furthermore, the spinal venous system appears to have an impact on spinal cord perfusion and it is as well as shown in compression experiments (Jellinger, ; Griessenauer et al, ).…”
Section: Introductionmentioning
confidence: 77%
“…However, a different study showed that reperfusion of the cord after a compressive insult is not accompanied by the recovery of evoked potentials (Hitchon et al, ). Furthermore, the spinal venous system appears to have an impact on spinal cord perfusion and it is as well as shown in compression experiments (Jellinger, ; Griessenauer et al, ).…”
Section: Introductionmentioning
confidence: 77%
“…Peripheral neuropathy in diabetes is the most common complication of both type 1 and type 2 diabetes1,2 and can affect peripheral sensory neurons in a large percent of adult diabetic patients,2 who may experience excessive sensitivity to nociceptive stimuli or perceive normal stimuli as painful stimuli 35. This often results in severely reduced quality-of-life measures 6…”
Section: Introductionmentioning
confidence: 99%
“…Through clinical correlations between both symptoms and lesions of the spine, along with early manipulative investigations, historical researchers were able to identify the spinal cord as an important conduit for signals to and from the brain. Contemporary researchers [2,[11][12][13][14][15][16][17] have used investigative techniques that have gone beyond surgical manipulation and stimulation to visualize the various components of the central Fig. 1 and cover figure Collage demonstrating physicians who have studied the spinal cord over human history.…”
Section: Resultsmentioning
confidence: 99%